Matching Structure with Strategy - Kozák, Tamás (Marketing & Menedzsment, 2019)
There is not one beatific receipt for a successful organizational form. The articulation of an organization, the complexity of the decision procedures, and the governance mechanisms depend basically on the operational environment and the proprietary expectations. At every firm, the fundamental standing points of estimation are the value chain and the efficacy of creating added values - in the same time there may be such special aspects that have significant effects on the requirements of an organization’s development. For example, think about the operational and organizational characteristics of a public transport service company. In companies like that the safety rules and requirements are so strictly regulated that they can overwrite other, e.g. financial and profitability aspects. Differential characteristics can be recognized between private and government corporations typically operating in competitive environment.